Penerapan Media Pembelajaran Audio Visual Dalam Meningkatkan Pemahaman Pelajaran Akidah Akhlak Siswa Kelas VII MTs Yaspen Muslim Pematang Tengah - Auliana Rizki, Usmaidar, Endah Retno Suci (Jurnal Pusat Studi Pendidikan Rakyat, 2022)
Audio-visual learning media in the form of video is a variable that is used to improve understanding of the lessons of faith and morality in the material of prayer and dhikr for seventh grade students of MTs Yaspen Muslim Pematang Tengah. The subjects of this study were the class VII students of MTs Yaspen Muslim Pematang Tengah, totaling 32 people. This research was conducted in two cycles, where each cycle consists of planning, acting, observing and reflecting. From the analysis of the data that the writer got, it was known that the initial condition was that in class VII of MTs Yaspen Muslim Pematang Tengah there was a problem, namely student learning outcomes in the subjects of aqidah, morality, the material of prayer and dhikr which were low and far from the KKM set by the Madrasah. In the pre-cycle implementation, the students' average score was 63.28 with 37.5% completeness. Then the first cycle was carried out, from the classroom action research data, there was an increase in the average value in the first cycle to 68.90 with a total completeness of 65.62%. Continued to the second cycle of action, in this action there was an increase again, namely the average score of 77.03 students with 90.62% completeness. This shows that the audio-visual learning media in the form of videos that the researchers used were able to improve understanding of the lessons of aqidah morals material for prayer and dhikr for the seventh grade students of MTs Yaspen Muslim Pematang Tengah, although not yet 100%.